Formulation of a Floating Drug Delivery System for Sustained Release Delivery of Methotrexate Using Manihot Esculenta Starch - OYENIYI, Yinka James; Emmanuel C Omenazu; Rabiu TG; Andrew Onu (AlQalam Journal of Medical and Applied Sciences, 2025)
The management of rheumatoid arthritis (RA) using methotrexate (MTX) is limited by poor oral bioavailability, dose-dependent toxicity, and gastrointestinal side effects. This study aimed to formulate and evaluate a methotrexate floating drug delivery system (FDDS) using Manihot esculenta (cassava) starch as a natural polymer to enhance gastric retention and sustain drug release. Cassava starch was extracted and characterized before its use in the preparation of floating microspheres via the ionic gelation method. Microspheres were formulated using pregelatinized cassava starch and sodium alginate with varying polymer ratios (1:1 and 1:2) and stirring speeds (300 and 600 rpm). The microspheres were evaluated for physicochemical and micromeritic properties, buoyancy, swelling index, floating lag time, total floating duration, entrapment efficiency, and in vitro drug release kinetics. All formulations exhibited good flow and spherical morphology. Floating lag times ranged from 2.8 to 4.4 min, with total floating durations exceeding 19 h. Entrapment efficiencies ranged from 57% to 81%, and swelling indices from 152% to 259%. In-vitro drug release profiles indicated sustained release over 18 h, best fitting the zero-order (R² = 0.992–0.997) and Korsmeyer-Peppas (R² = 0.986–0.993) models, suggesting super case-II transport dominated by polymer relaxation and erosion. Optimized cassava starch-based floating microspheres demonstrated prolonged gastric retention and sustained MTX release, highlighting the potential of Manihot esculenta starch as a biodegradable, cost-effective polymer for enhancing oral methotrexate therapy in RA management.